Enhanced Radiation Sensitivity of Human Papillomavirus-Driven Head and Neck Cancer: Focus on Immunological Aspects - Özcan-Wahlbrink, Mine; Schifflers, Christoph; Riemer, Angelika B. (Frontiers in Immunology, 2019)
Head and neck squamous cell carcinomas (HNSCC), emerging in the epithelial cells of the mucous membrane of the upper aerodigestive tract, are associated with either the classical risk factors, which are tobacco and alcohol use, or infections with high-risk types of the human papillomavirus (HPV). Depending on the involvement of HPV, HNSCC follow diverse carcinogenesis pathways and represent distinct clinical presentations. This difference between HPV-driven and HPV-negative HNSCC is most pronounced in survival, prognosis and outcome of therapy. Besides having better survival rates and prognosis, HPV-driven HNSCC have been shown to have enhanced radiation responses, compared to their radioresistant HPV-negative counterparts. Although radiosensitivity of HPV-driven HNSCC has been studied by many research groups, the major causes for the difference in radiation responses in HPV-driven and HPV-negative HNSCC are still an open question. In this mini review, we discuss the reported cellular and immunological effects of the enhanced radiation response in HPV-driven HNSCC and focus on the vital role of immune responses in the outcome of HNSCC radiation therapy.